Estudo da ocorrência da leishmaniose cutânea em humanos e a taxa de infecção em flebotomíneos no sul de Roraima (municípios de São João da Baliza e São Luiz do Anauá), Brasil - Rocha, Miriam (Entomologia, 2020)
The American Cutaneous Leishmaniasis is a disease of chronic evolution, caused by protozoa from the genus Leishmania, its transmission to man, occurs by the bite of sandflies (Diptera: Psychodidae). The research aimed to study the incidence of human cases of American Cutaneous Leishmaniasis (ACL) in the south of the state of Roraima, in the cities of São João da Baliza and São Luiz do Anauá. The risk areas were determined by applying a structured interview concomitant with an educational program as a preventive factor to the identified residents with and without ACL, living 200 meters from the forest border. It has been performed a dissection in the insect's digestive tract in search of the protozoa, followed by intradermal inoculation techniques in the laboratory test subject, hamsters (Mesocricetus auratus), and possible isolation on Novy and McNeal's modified blood agar by Nicolle (NNN). This study describes 68 cases of ACL in humans that occurred in two municipalities, detected and registered between 2003 and 2005, whose identification and diagnosis were carried out at the Fundação Nacional de Saúde (FNS) and Secretaria de Saúde do Estado (SUSAM). The diagnosis consisted of 68 patients (94%) who had positive results in the direct search for the parasite and five patients (6%) who had negative results, but afterwards they underwent Montenegro's intradermoreaction and were confirmed as positive after 72 hours, all patients had skin lesions, most of them were predominantly in the lower limbs. There were 49 ACL cases in São João da Baliza and 19 in São Luiz do Anauá in this study. During this investigation, sampling of sandflies in the forest and housing areas was carried out in both cities during the referred period using light traps of the CDC type, Shannon's trap with animal bait at 100 meters from the forest border and a Castro type vacuum for the collections made at the base of the tree. In São João da Baliza, 4,960 specimens were collected, and 5,703 in São Luiz do Anauá, the total specimens collected were 10,487 corresponding to 5,967 females and 4,520 male sandflies belonging to the genera: Lutzomyia, França and Parrot (1924). As for the infection rate, the variation at the border of the forest was 4.16% and 4.3%, in the interior was 4.61% and 3.51%. Keywords: Transmission, Natural Infection, Sandflies.
Keywords: Flebotomíneos